Youth Participation in Governance and Structural Economic Transformation in Zimbabwe - Masarurwa, Hillary Jephat (African Journal of Stability and Development (AJSD), 2018)
This paper, Youth Participation in Governance and Structural Economic Transformation in Zimbabwe, assesses the level of participation in economic, elections and governance processes by Zimbabwean youth. It also depicts the barriers to such participation and issues that youths view as important to them. Finally, it proposes solutions that can be applied to achieve youth-inclusive structural transformation and enhance their participation therein. The study was carried out using quantitative methodologies. A survey was carried out to collect data, which in turn was analysed using SPSS. The analysis finds evidence that youth participation is low across all sectors. The youths are economically side-lined, largely unemployed and living in poverty given the low income they earn. They lack skills in business management, vocational and technical areas, civic education, elections as well as skills on how to engage government. Their participation in elections and governance processes is low and it is hampered by restrictive political structures, lack of interest, lack of information and lack of funds amongst other things. It was observed that decision making processes are not improving in becoming more participatory and youth inclusive. Whilst some youths are ready to run for public office or start their own businesses, they need support for their participation to be meaningful. The youths need space to freely participate in politics and development without restrictions as well as getting support through leadership training. Policymakers need to design programmes that close the skills gap, give youths more access to means of production and support them to be employment creators.